Anti-U1RNP-70kD-positive case of neonatal lupus presenting with seizure and incomplete heart block: a case report and literature review - Alfalasi, Maryam; ElGhazali, Gehad; Fathalla, Waseem; Khawaja, Khulood (Frontiers in Pediatrics, 2023)
Neonatal lupus erythematosus (NLE) is an autoimmune disease caused by the transplacental passage of anti-Ro/SS-A and anti-La/SS-B, this can be less commonly seen with U1-ribonucleoprotein (U1RNP). Our case is of a 7-day old male, who first presented with seizures, in addition, during the electroencephalogram (EEG), he was found to have an irregular heart rhythm. Looking further into the history, we found the mother was aware that she had systemic lupus erythematosus (SLE), however, she had not been following up with a rheumatologist. The workup for NLE found negative anti-Ro/SS-A and anti-La/SS-B, with positive U1RNP-70kD. U1RNP-70kD is diagnostic for mixed connective tissue disease in adults, but no research has been done on its significance in NLE. The infants’ mother; despite having SLE, did not receive surveillance during her pregnancy, as the current guidelines are tailored for mothers with anti-Ro/SS-A and anti-La/SS-B. As a result, this calls for the extension of these guidelines to include the U1RNP-70kD antibody. In this case, the 70kd subtype of U1RNP was positive, which may have had a role to play in this unusual presentation; however, further research is needed to improve the care of mothers and babies with U1RNP-70kD.